The influence of motivation on the teaching performance and identity construction of an EFL Student Teacher (2023)
This research project explores the influence of motivation on the teaching performance and identity construction of an English as a Foreign Language (EFL) student teacher. Using autoethnography as the chosen methodology, the study focuses on one private university in Medellín, Colombia, and the Colombo Americano Downtown Center as the primary contextual settings. The sole participant in this research is the researcher herself. Three key findings emerged from the study: Firstly, the participant’s motivation was evident in her choice of English as a career and her willingness to persist despite occasional lack of complete motivation, driven by familial expectations. Secondly, levels of anxiety and confidence varied based on three main factors. Lastly, two types of influences on motivation were identified: immediate and distant. In conclusion, in light of the self-development theory, motivation was found to be a dynamic element influenced by rewards, punishment, ego-following (Niemiec & Ryan, 2009), and job opportunities related to the chosen career path.